Navigating power in outreach youth work: Relationship-based approaches to substance use prevention - Chabchoub, Jonas; Jacobsen, Cathrine Sundal; Haugstvedt, Håvard (Addicta: The Turkish Journal on Addictions, 2026)
Outreach youth work, defined as relationship-based social work conducted in young people’s own environments, aims, among other things, to identify and prevent substance use by building relationships and connecting individuals to relevant services. This is critical when engaging marginalized groups, such as migrant and refugee youth, who may face vulnerabilities related to resettlement, trauma, and social exclusion, as well as youth in open drug scenes, with a high prevalence of adverse childhood experiences. The task has an inherent tension between providing support and exerting varying degrees of professional power, which may shape how outreach youth workers sustain their relevance in contexts where substance use holds meaning for youth. This article draws on two qualitative studies based on semi-structured interviews and focus groups with 12 outreach youth workers from a large outreach service in a major Norwegian city. Both studies explored relationship-building in marginalized urban environments, and the combined analysis examined how power influences outreach youth workers’ ability to prevent substance use.The analysis indicates that outreach youth workers are well-positioned to reach and build relationships with youth, such as youths involved in buying, selling, and using illegal substances. Power dynamics play a significant role in this interaction. Enduring rejection, professional transparency, and professional reflection may reduce the impact of power when building relationships. Finally, we propose how the article’s findings can be integrated into practice and recommend future research.
Keywords: outreach youth work; relationships; youth in marginalized environments; power